Porous organic material and preparation method thereof
By using hydroxyl-containing water-soluble organic compounds to make pores, the side chain cyano-containing organic polymers are formed to form porous porous organic materials, which solves the problem of insufficient thermal conductivity of low dielectric materials, and achieves reduction of dielectricity and improvement of thermal conductivity. Improves the stability of electronic devices.
Patent Information
- Application Number
- CN202411528647.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-10
AI Technical Summary
Existing low dielectric materials have low thermal conductivity in high-frequency applications, resulting in severe signal attenuation and reducing the stability of electronic devices.
The pore-forming side chains containing cyano-organic polymers are used to use water-soluble organic substances containing hydroxyl groups as pore-forming agents. Through drying, water washing and low-temperature freeze-drying steps, a porous organic material with high crystallinity is formed, reducing dielectricity and improving thermal conductivity. coefficient.
The thermal conductivity of porous organic materials is significantly improved, while reducing the dielectric constant and density, enhancing the stability and thermal conductivity of the material.
Smart Images

Figure CN119286048A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of low dielectric materials, and in particular to a porous organic material and a preparation method thereof. Background Art
[0002] With the advent of the 5G era, the ultra-large-scale integrated circuit and microelectronics industries are developing rapidly, which urgently requires the device feature size to be gradually reduced, that is, the higher the circuit integration, but also brings a series of new technical problems such as signal transmission crosstalk and interconnect resistance-capacitance delay. At present, the development of high-performance low-dielectric and even ultra-low-dielectric materials for 5G has become a research hotspot in the field of microelectronics.
[0003] Currently, a variety of low dielectric materials have been developed on the market to meet these requirements, such as silicates, polymer-based composites, porous materials, ceramic materials, etc. Although these materials perform well in terms of low dielectric properties, they have low thermal conductivity, which leads to poor heat dissipation of electronic devices, causing serious signal attenuation in high-frequency applications and reducing the stability of electronic devices. Summary of the invention
[0004] In view of the deficiencies of the above-mentioned related technologies, the present application provides a porous organic material and a preparation method thereof. The present application uses a water-soluble organic substance containing a hydroxyl group as a porogen to form pores in an organic polymer containing a cyano group in a side chain, thereby obtaining a porous organic material with high crystallinity, thereby reducing the dielectric property of the porous organic material and improving the thermal conductivity of the porous organic material.
[0005] In the first aspect, the present application provides a porous organic material using the following technical solution: A porous organic material comprises an organic polymer treated with a porogen to form pores, wherein the side chain of the organic polymer contains a cyano group, and the porogen is a water-soluble organic substance containing a hydroxyl group.
[0006] Preferably, the porogen includes one or more of polyethylene glycol, polyvinyl alcohol, polypropylene alcohol, polyglycolic acid, polyethylene terephthalate, polyamino acid polymers, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, glycerol, isopropanol and solutions of the above substances.
[0007] Preferably, the organic polymer includes one or more of polyacrylonitrile, polyvinylnitrile, polystyrenenitrile, polycyanostyrene and poly-(N-cyanoacrylamide).
[0008] Preferably, the porosity of the porous organic material is 28%-85%.
[0009] In a second aspect, the present application provides a method for preparing a porous organic material using the following technical solution: A method for preparing a porous organic material comprises the following steps: taking an organic polymer to prepare a polymer solution, mixing a porogen with the polymer solution to obtain a mixed solution, placing the mixed solution in a mold and drying it to obtain a mixture, washing the mixture with water, soaking it, and then drying it to obtain the organic porous material.
[0010] Preferably, the mass fraction of the organic polymer in the polymer solution is 1%-20%.
[0011] Preferably, the mass fraction of the polymer solution includes one of 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18% and 20%.
[0012] Preferably, the porogen comprises pure organic matter or a solution of pure organic matter.
[0013] Preferably, the porogen is a polyethylene glycol solution with a molecular weight of Mn=2000 g / mol.
[0014] Preferably, the volume ratio of the polymer solution to the porogen is 5-150:1.
[0015] Preferably, the volume ratio of the polymer solution to the porogen is 15:1.
[0016] Preferably, the drying temperature is 60-100° C. and the drying time is 10-120 min.
[0017] Preferably, the soaking time of the water washing and soaking is 20-26 hours, and the soaking water is replaced every 5-7 hours.
[0018] Preferably, the soaking time of the water washing and soaking is 24 hours, and the soaking water is replaced every 6 hours.
[0019] Preferably, the drying comprises freeze-drying.
[0020] Preferably, the freeze-drying temperature is minus 50-60° C., the vacuum degree is 1 Pa, and the freeze-drying time is 24 hours.
[0021] In this application, the porous organic material is based on a polymer containing a cyano side chain and a carbon-carbon single bond as the skeleton. Since the main chain skeleton of the polymer is connected together by carbon-carbon single bonds, the polymer chain shows a certain flexibility and will be entangled and stacked together in a disordered manner in the form of a "ball of yarn" to form amorphous particles. As a strong polar functional group, the cyano group makes the molecular chains and the chains show a certain mutual repulsion. Under the action of the two, although this type of polymer presents a granular microscopic morphology, the crystallinity is low.
[0022] After adding a hydroxyl-containing water-soluble porogen to the polymer solution, the polarity difference between the hydroxyl group and the cyano group promotes the formation of hydrogen bonds between the porogen and the polymer molecular chain. Under the action of hydrogen bonds, the mutual repulsion of the cyano functional groups on the polymer molecular chain is weakened, untangling the disordered "wool ball" of the polymer chain, allowing the organic polymer molecular chain skeleton to be thoroughly stretched in the solvent system, further reducing the crystallinity of the polymer. The mixed solution is dried to remove the solvent, allowing the organic polymer and the porogen to fully contact and form large droplets of organic polymer-porogen.
[0023] The mixture of organic polymer and porogen is then washed and soaked in water. Since the porogen is a water-soluble organic substance, the porogen droplet particles in the system are replaced by water, thereby introducing water liquid into the organic polymer system. During the water washing process, the large droplets of organic polymer-porogen are gradually desolvated, allowing the flexible organic polymer molecular chains to re-assemble into more ordered crystals and precipitate, thereby improving the crystallinity of the organic polymer. Finally, after low-temperature freeze-vacuum drying, a porous organic material with high crystallinity is obtained.
[0024] Due to the presence of pores, the dipole moment density and refractive index per unit volume of the porous organic material are reduced, so the dielectric constant and density of the porous organic material are reduced at the same time. During the desolvation process, the crystallinity of the porous organic material is significantly improved, that is, the order of the material is improved, and a crystalline framework network is constructed inside the system. This highly ordered crystalline network can effectively suppress phonon vibrations during heat transfer and act as an effective heat conduction path, thereby improving the thermal conductivity of the porous organic material.
[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. The present application uses a water-soluble organic substance containing a hydroxyl group as a porogen to form pores in an organic polymer containing a cyano group in the side chain, thereby obtaining a porous organic material with high crystallinity, thereby reducing the dielectric properties of the porous organic material and improving the thermal conductivity of the porous organic material.
[0026] 2. The present application facilitates the formation of pores in the organic polymer material by mixing the organic polymer solution with the porogen and then drying, immersing in water, and drying, thereby reducing the dipole moment density and refractive index per unit volume of the porous organic material. Therefore, the dielectric constant and density of the porous organic material are simultaneously reduced.
[0027] 3. The present application uses water-soluble organic matter containing hydroxyl groups to perform pore-forming treatment on organic polymers containing cyano groups, and utilizes the polarity difference between hydroxyl groups and cyano groups to promote the stretching and re-self-assembly of organic polymer molecular chains, thereby improving the crystallinity of porous organic materials and improving the thermal conductivity of porous organic materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a comparison diagram of the appearance of comparative example 1 and embodiment 1. Figure 1 (a), Example 1 is Figure 1 (b); Figure 2 is a comparison of the scanning electron microscope images of comparative example 1 and embodiment 1, where comparative example 1 is Figure 2 (a), Example 1 is Figure 2 (b); Figure 3 is a curve showing the variation of thermal conductivity with porosity of Examples 1-8 and Comparative Example 1; Figure 4 It is a comparison chart of the dielectric constant variation curves of Examples 1-8 and Comparative Example 1 with the electric field frequency. DETAILED DESCRIPTION
[0029] The present application is further described in detail below in conjunction with examples. The following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. In the following examples, if specific conditions are not specified, they are carried out according to normal conditions or conditions recommended by the manufacturer. The methods used are conventional methods known in the art unless otherwise specified, and the consumables and reagents used are commercially available unless otherwise specified. Unless otherwise specified, the professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the recorded content may also be applied to the present invention.
[0030] The raw materials used in the examples and comparative examples can all be obtained commercially.
[0031] Example 1 Example 1 of the present application provides a porous organic material, and the preparation steps are as follows: Take 0.2g of polyacrylonitrile (PAN) powder and dissolve it in 9.8g of N,N-dimethylformamide (DMF) solvent and place it in a solvent bottle, then stir it overnight in a water bath at 50℃ until it is clear and transparent to obtain a polymer solution with a mass fraction of 2.0wt%. Measure 3.0ml of the polymer solution, add 0.1ml of porogen (polyethylene glycol (PEG) with Mn=300g / mol, because PEG at this molecular weight is in liquid state, it is directly measured and used), and ultrasonicate for half an hour to obtain a mixed solution. Measure 1.5ml of the mixed solution and inject it into a 4.0cm×4.0cm×0.2cm mold, then place it in a blast drying oven at 70℃ for 30 minutes, remove DMF, and obtain a film-like mixture. The mixture was placed in a sufficient amount of deionized water and thoroughly washed and soaked to remove PEG and residual DMF. The washing time was 24 hours, and the deionized water was replaced every 6 hours to obtain a wet porous organic material. The wet porous organic material was placed in a vacuum freeze drying oven and freeze-dried for 24 hours at -60°C and a vacuum degree of 1 Pa to avoid shrinkage of the pores to obtain a porous organic material.
[0032] Example 2 Example 2 of the present application provides a porous organic material, and the preparation steps are as follows: Take 0.2g of polyacrylonitrile (PAN) powder and dissolve it in 9.8g of N,N-dimethylformamide (DMF) solvent and place it in a solvent bottle, then stir it overnight in a water bath at 50℃ until it is clear and transparent to obtain a polymer solution with a mass fraction of 2.0wt%. Take 1.0g of polyethylene glycol (PEG) particles with a molecular weight of Mn=2000g / mol and dissolve it in 1.0g of N,N-dimethylformamide (DMF) solvent and place it in a solvent bottle, stir it at room temperature until the solution is clear and transparent to obtain a porogen. Measure 3.0ml of the polymer solution, add 0.2ml of the porogen, and ultrasonicate for half an hour to obtain a mixed solution. Measure 1.5ml of the mixed solution and inject it into a 4.0cm×4.0cm×0.2cm mold, then place it in a blast drying oven at 100℃ for 10 minutes, remove DMF, and obtain a film-like mixture. The mixture was placed in sufficient deionized water for thorough washing and soaking to remove PEG and residual DMF. The washing time was 24 hours, and the deionized water was replaced every 6 hours to obtain a wet porous organic material. The wet porous organic material was placed in a vacuum freeze drying oven and freeze-dried for 24 hours at -60°C and a vacuum degree of 1Pa to avoid shrinkage of the pores to obtain a porous organic material.
[0033] Example 3 Example 3 of the present application provides a porous organic material, and the preparation steps are as follows: Take 0.4g of polyacrylonitrile (PAN) powder and dissolve it in 9.6g of N,N-dimethylformamide (DMF) solvent and place it in a solvent bottle, then stir it overnight in a water bath at 50℃ until it is clear and transparent to obtain a polymer solution with a mass fraction of 4.0wt%. Measure 3.0ml of the polymer solution, add 0.08ml of porogen (small molecule polyol 1,2-propylene glycol (PDO), because PDO is in liquid state, it is directly measured and used), and ultrasonicate for half an hour to obtain a mixed solution. Measure 2ml of the mixed solution and inject it into a 4.0cm×4.0cm×0.2cm mold, then place it in a blast drying oven at 60℃ for 2 hours, remove DMF, and obtain a film-like mixture. The mixture was placed in a sufficient amount of deionized water and thoroughly washed and soaked to remove PDO and residual DMF. The washing time was 24 hours, and the deionized water was replaced every 6 hours to obtain a wet porous organic material. The wet porous organic material was placed in a vacuum freeze drying oven and freeze-dried for 24 hours at -60°C and a vacuum degree of 1 Pa to avoid shrinkage of the pores to obtain a porous organic material.
[0034] Example 4 Example 4 of the present application provides a porous organic material. The difference between Example 4 and Example 1 is that during the preparation process, 3.0 ml of polymer solution is measured and 0.02 ml of porogen is added thereto.
[0035] Example 5 Example 5 of the present application provides a porous organic material. The difference between Example 5 and Example 1 is that during the preparation process, 3.0 ml of the polymer solution is measured and 0.04 ml of the porogen is added thereto.
[0036] Example 6 Example 6 of the present application provides a porous organic material. The difference between Example 6 and Example 1 is that during the preparation process, 3.0 ml of polymer solution is measured and 0.06 ml of porogen is added thereto.
[0037] Example 7 Example 7 of the present application provides a porous organic material. The difference between Example 7 and Example 1 is that during the preparation process, 3.0 ml of the polymer solution is measured and 0.14 ml of the porogen is added thereto.
[0038] Example 8 Example 8 of the present application provides a porous organic material, and the preparation steps are as follows: Take 0.2g of polystyrene nitrile (PSAN) powder and dissolve it in 9.8g of N,N-dimethylformamide (DMF) solvent and place it in a solvent bottle, then stir it overnight in a water bath at 50℃ until it is clear and transparent to obtain a polymer solution with a mass fraction of 2.0wt%. Measure 3.0ml of the polymer solution, add 0.20ml of porogen (small molecule polyol 1,2-propylene glycol (PDO), because PDO is in liquid state, it is directly measured and used), and ultrasonicate for half an hour to obtain a mixed solution. Measure 1.5ml of the mixed solution and inject it into a 4.0cm×4.0cm×0.2cm mold, then place it in a blast drying oven at 70℃ for 30 minutes to remove DMF to obtain a film-like mixture. The mixture was placed in a sufficient amount of deionized water and thoroughly washed and soaked to remove PDO and residual DMF. The washing time was 24 hours, and the deionized water was replaced every 6 hours to obtain a wet porous organic material. The wet porous organic material was placed in a vacuum freeze drying oven and freeze-dried for 24 hours at -60°C and a vacuum degree of 1 Pa to avoid shrinkage of the pores to obtain a porous organic material.
[0039] Comparative Example 1 Comparative Example 1 of the present application provides an organic material, and the preparation steps thereof are as follows: Take 0.2g of polyacrylonitrile (PAN) powder and dissolve it in 9.8g of N,N-dimethylformamide (DMF) solvent and place it in a solvent bottle, then stir it overnight in a water bath at 50℃ until it is clear and transparent to obtain a polymer solution with a mass fraction of 2.0wt%. Measure 1.5ml of the polymer solution and inject it into a 4.0cm×4.0cm×0.2cm mold, then place it in a blast drying oven at 70℃ for 12 hours to remove DMF and obtain a film-like polymer. Place the polymer in sufficient deionized water and thoroughly wash and soak it for 2 hours to obtain a wet organic polymer material. Place the wet organic polymer material in a vacuum freeze drying oven and freeze-dry it for 24 hours at minus 60℃ and a vacuum degree of 1Pa to obtain an organic material.
[0040] Test and Inspection The porous organic material of Example 1 and the organic material of Comparative Example 1 were imaged by scanning electron microscope, and a comparison diagram of the scanning electron microscope images of the porous organic material of Example 1 and the organic material of Comparative Example 1 was obtained. Figure 2 The porosity, dielectric constant and thermal conductivity of the porous organic materials of Examples 1-8 and the organic material of Comparative Example 1 were respectively detected, as shown in Table 1 below, and the curve of thermal conductivity changing with porosity was obtained by analysis, as shown in Table 1 below. Figure 3 As shown in Table 1:
[0041] The dielectric constants of the porous organic materials of Examples 1-8 and the organic material of Comparative Example 1 at different electric field frequencies were measured respectively, and a comparison graph of the curves of the dielectric constant changing with the electric field frequency was obtained, as shown in FIG. Figure 4 Results Analysis The following combination Figure 1-4 And the experimental results provided in Table 1 are used to explain this application in detail.
[0042] Depend on Figure 1 It can be seen that the organic material of Comparative Example 1 is in the form of a transparent film, and the porous organic material of Example 1 is in the form of a white film with a flat surface and no wrinkles.
[0043] Reference Figure 2 It can be seen that the porous organic material of Example 1 has uniformly dispersed holes inside, and the micro-nano crystal morphology of the organic material in Comparative Example 1 has been significantly changed. The size of the micro-nano particles of the organic material in Comparative Example 1 is 50-100nm, with clear boundaries, randomly scattered inside the material, and its crystallinity is only 7.1%. The micro-nano particles in the organic porous material of Example 1 are all integrated, and the particle size increases to 500nm-1000nm, while the crystallinity of the porous organic material of Example 1 increases to 21.2%, which is about 3 times higher, and the crystalline particles are bridged together to form a connected heat conduction path. Therefore, the thermal conductivity of the porous organic material of Example 1 is significantly improved compared to Comparative Example 1.
[0044] Referring to Table 1, it can be seen that the dielectric constants of the porous organic materials of Examples 1-8 are reduced by nearly 26%-75% compared with the dielectric constants of the organic materials of Comparative Example 1, especially the dielectric constants of Examples 1-3 and Example 7 with porosities of 61.6%-73.7% are only 27%-35% of the organic materials of Comparative Example 1, indicating that the use of water-soluble organic matter containing hydroxyl groups as porogens to form pores and treat organic polymers containing cyano groups in side chains is beneficial to reducing the dielectric constants of porous organic materials. Referring to Tables 3 and Figure 3 The thermal conductivity of the porous organic materials in Examples 1-7 is nearly 10 times that of the organic material in Comparative Example 1, and the thermal conductivity of the porous organic material in Example 2 reaches a maximum value of 1.84 W / m·K, which further illustrates that the use of water-soluble organic matter containing hydroxyl groups as a pore-forming agent to form pores in the side chain of an organic polymer containing cyanide groups greatly improves the thermal conductivity of the porous organic materials.
[0045] Reference Figure 4It can be seen that the variation range of the dielectric constant of the porous organic materials in Examples 1-8 of the present application in electric fields of different frequencies is smaller than the variation range of the dielectric constant of the organic materials in Comparative Example 1 in electric fields of different frequencies, indicating that the stability of the dielectric constant of the porous organic materials in Examples 1-8 in electric fields of different frequencies is higher than the stability of the dielectric constant of the organic materials in Comparative Example 1 in electric fields of different frequencies, especially Examples 1-3 and Examples 7-8, indicating that the use of water-soluble organic matter containing hydroxyl groups as a pore-forming agent to form pores in organic polymers containing cyanide groups in side chains is beneficial to improving the stability of the dielectric constant of the porous organic materials in electric fields of different frequencies.
[0046] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A porous organic material, characterized in that: The invention comprises an organic polymer treated with a porogen to form pores, wherein the side chain of the organic polymer contains a cyano group, and the porogen is a water-soluble organic substance containing a hydroxyl group.
2. A porous organic material according to claim 1, characterized in that: The porogen includes one or more of polyethylene glycol, polyvinyl alcohol, polypropylene alcohol, polyglycolic acid, polyethylene terephthalate, polyamino acid polymers, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, glycerol, isopropanol and solutions of the above substances.
3. A porous organic material according to claim 1, characterized in that: The organic polymer includes one or more of polyacrylonitrile, polyvinyl nitrile, polystyrene nitrile, polycyanostrene and poly-(N-cyanoacrylamide).
4. A porous organic material according to claim 1, characterized in that: The porosity of the porous organic material is 28%-85%.
5. A method for preparing a porous organic material according to claims 1 to 4, characterized in that: The method comprises the following steps: preparing a polymer solution by taking an organic polymer, mixing a porogen with the polymer solution to obtain a mixed solution, placing the mixed solution in a mold and drying it to obtain a mixture, washing, soaking and drying the mixture to obtain the organic porous material.
6. The method for preparing a porous organic material according to claim 5, characterized in that: The mass fraction of the organic polymer in the polymer solution is 1%-20%.
7. The method for preparing a porous organic material according to claim 5, characterized in that: The volume ratio of the polymer solution to the porogen is 5-150:
1.
8. The method for preparing a porous organic material according to claim 5, characterized in that: The drying temperature is 60-100° C. and the drying time is 10-120 min.
9. The method for preparing a porous organic material according to claim 5, characterized in that: The soaking time of the water washing and soaking is 20-26 hours, and the soaking water is replaced every 5-7 hours.
10. The method for preparing a porous organic material according to claim 5, characterized in that: The drying includes freeze-drying.